Integrating Indigenous Cultural Dance into Elementary Character Education: Evidence from Torata Dance Learning in Indonesia - Salsabila Salsabila; Andi Imrah Dewi; Kadek Hariana; Zulnuraini Zulnuraini; Kasmawati Kasmawati (Journal of Innovation and Research in Primary Education, 2026)
This study examined the role of Torata Dance-based learning in fostering character education among elementary school students at SD Negeri Tondo, Palu, Central Sulawesi, Indonesia. The study was motivated by the persistent gap in empirical research on how specific local traditional dances function as systematic pedagogical instruments for character formation. A qualitative descriptive design was employed, involving 29 third-grade students and one arts teacher as participants. Data were collected through structured observation, semi-structured interviews, and documentation, and analyzed using Miles et al.'s interactive model. Findings reveal that Torata Dance instruction, delivered through culturally mediated sequential stages, cultivated five core character values — religiosity, discipline, responsibility, love for the homeland, and social care — through embodied practice and teacher-guided cultural explanation. A particularly notable finding is that value internalization was not a spontaneous outcome of dance participation but was systematically shaped by the teacher's pedagogical intentionality and capacity to integrate cultural meanings into instructional sequences. These results affirm that local cultural dance, when pedagogically mediated, constitutes an effective and contextually relevant vehicle for holistic character education, contributing empirical evidence to discussions on culturally responsive pedagogy and arts-based moral formation in elementary schooling.